Epidemiological features of brucellosis in the Republic of Azerbaijan at the present stage - Elchin Huseynov Mammad oglu (Kazimierz Wielki University, 2018)
Modern brucellosis is characterized by high variability of clinical symptoms. The evolution of brucellosis in modern conditions is heading in the direction of acute brucellosis increasing in its frequency with the early development of focal metastatic and infectious-allergic lesions, which increase the severity of the disease. The purpose of our study was to analyze the epidemiological features of acute brucellosis in the Republic of Azerbaijan. Of the 178 patients surveyed, only 120 persons fully met the criteria, which formed the main group. Statistical analysis of the results of the study was performed using the programs "SPSS 20.0", "STATISTICA 6.0". Acute brucellosis was found to be 7.5 times more frequent in women aged 40 to 49 years (p